2011
DOI: 10.1038/mt.2010.258
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Safety Evaluation of AAV2-sFLT01— A Gene Therapy for Age-related Macular Degeneration

Abstract: AAV2-sFLT01 is a vector that expresses a modified soluble Flt1 receptor designed to neutralize the proangiogenic activities of vascular endothelial growth factor (VEGF) for treatment of age-related macular degeneration (AMD) via an intravitreal injection. Owing to minimal data available for the intravitreal route of administration for adeno-associated virus (AAV), we initiated a 12-month safety study of AAV2-sFLT01 administered intravitreally at doses of 2.4 × 10(9) vector genomes (vg) and 2.4 × 10(10) vg to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
126
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 27 publications
(28 reference statements)
2
126
1
Order By: Relevance
“…A recent study in non-human primates using a similar vector, AAV2.sFlt01, injected intravitreally, showed the vector to be safe overall, but a higher level of inflammation and immune response 50 than we report here was found. Whereas AAV2.sFlt-1 described here encodes the naturally occurring form of the soluble receptor driven by the CMV promoter, AAV2.sFLT01 encodes only one Flt-1 domain 2 linked by 9Gly to a human IgG1 heavy-chain Fc domain to generate a forced homodimer and is expressed by the chicken b-actin promoter.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…A recent study in non-human primates using a similar vector, AAV2.sFlt01, injected intravitreally, showed the vector to be safe overall, but a higher level of inflammation and immune response 50 than we report here was found. Whereas AAV2.sFlt-1 described here encodes the naturally occurring form of the soluble receptor driven by the CMV promoter, AAV2.sFLT01 encodes only one Flt-1 domain 2 linked by 9Gly to a human IgG1 heavy-chain Fc domain to generate a forced homodimer and is expressed by the chicken b-actin promoter.…”
Section: Discussioncontrasting
confidence: 56%
“…Thus, the potential production of low amounts of sFlt-1 protein in the optic nerve is unlikely to represent any risk. Thus, our study on non-human primates demonstrated that, in contrast to intravitreally injected AAV2 constructs, 50 AAV2 constructs injected into the subretinal space remained localized in the eye. Density plots of B-cell populations (CD21 þ ) Ki67 expression are shown for two animals in the study, one AAV2.sFlt-1 treated and the other AAV2.GFP treated.…”
Section: Discussionmentioning
confidence: 99%
“…25,43 For example, a recent study suggested that the engineered AAV variant AAV2-7m8 might be more immunogenic when used at high doses via intravitreal injections. 25 Therefore, we chose AAV2 for its known safety and efficacy in targeting RGCs in NHP studies [27][28][29] and the large body of work using this vector in human clinical trials. [20][21][22][23]44 High-level expression with a limited viral dose being a major parameter in obtaining functional expression, we designed a new RGC-specific promoter, driving strong transgene expression in RGCs.…”
Section: Discussionmentioning
confidence: 99%
“…This extended time point was chosen as previous studies established that after intravitreal delivery of AAV2, the transgene expression levels are stable after 6 months. 29 Based on this, we first wanted to examine whether the low dose (1 Â 10 11 vg) would lead to better functional results at 6 months. NHP5 was euthanized at 6 months post-injection and MEA was used to measure light responses as described previously.…”
Section: Catch-driven Light Responses At 6 Months Post-injectionmentioning
confidence: 99%
See 1 more Smart Citation